Silvopastoral systems in Brazil: a systematic review (Research, Society and Development, 2020)
This research aims to provide a history of advances and the diversity of dispersion of Silvipastoral Systems SPS in Brazil based scientific literature. The method used comprised a systematic literature review, using the Web of Science database. In total, 63 articles were selected based on inclusion and exclusion criteria, from an initial sample of 374. The analysis of the selected articles allowed the identification of 73 silvopastoral systems, distributed across all Brazilian geopolitical regions. The SPS were categorized according to the region, diversity and objectives of the studies. These objectives were animal based studies, pasture, tree, economic or SPS components. Finally, this systematic review allowed the development of an evidence map, demonstrating the knowledge gaps on the topic, and the need for further studies.